Evaluation of cutting patterns produced in primary teeth by an air-abrasion system - Peruchi, Cláudia; Santos-Pinto, Lourdes; Santos-Pinto, Ary; Barbosa E Silva, Emilio (My University, 2002)
Objective: The aim of this in vitro study was to assess the effect of tip diameter, nozzle distance, and application time of an air-abrasion system for cavity preparation on the enamel of primary teeth. Method and materials: Forty exfoliated primary teeth were air abraded with a microabrasion machine used with a handpiece with an 80-degree-angle nozzle, 50-μm abrasive particle size, and 80-psi air pressure. The effects of 0.38- or 0.48-mm inner tip diameter, 2- or 5-mm distance from tip to tooth surface, and 15 or 30 seconds of application time on cutting efficiency were evaluated. Cutting width and depth were analyzed and measured from scanning electron micrographs. Results: Statistical analysis revealed that the width of the cuts was significantly greater when the tip distance was increased. Significantly deeper cavities were produced by a tip with a 0.48-mm inner diameter. The application time did not influence the cuts. Conclusion: The cutting patterns found in this study suggest that precise removal of enamel in primary teeth is best accomplished when a tip with a 0.38-mm inner diameter is used at a 2-mm distance.
Keywords: Air abrasion; Cavity preparation; Primary tooth